Movement and Spiritual Transformation in Pilgrimage: A Phenomenological Study of Kalpwasis at Kumbh Mela - Nargis Khan (RaSAIL Media Group, Semarang, Indonesia, 2025)
This study investigates the role of movement in shaping spiritual transformation during the pilgrimage cycle of Kalpwasis at the Kumbh Mela, using them as the central unit of analysis. The research aims to examine how each stage of the journey—departing from home, engaging in ritual practices at the sacred site, and returning to everyday life—contributes to the spiritual awareness and long-term transformation of pilgrims. Employing a phenomenological qualitative approach, the study draws on in-depth interviews and open-ended questionnaires conducted with approximately 200 Kalpwasis who resided in the Kumbh Mela camp throughout the major bathing days of 2025. Data were analyzed thematically to identify recurring patterns of experience. Findings reveal that physical movement through sacred space, combined with ritual immersion and temporary withdrawal from worldly routines, fosters heightened spiritual discipline, emotional purification, and a renewed sense of identity. A significant insight of the study is the transformative impact of the return journey, where pilgrims integrate insights gained during Kalpwas into their everyday lives, reinforcing their commitment to spiritual growth. The study recommends further longitudinal and comparative research on post-pilgrimage reintegration and encourages a broader exploration of embodied movement within Indian pilgrimage traditions to deepen theoretical understanding of cyclical spiritual practices.